2002
DOI: 10.1074/jbc.m109604200
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like Growth Factor (IGF)-binding Protein-3 Mutants That Do Not Bind IGF-I or IGF-II Stimulate Apoptosis in Human Prostate Cancer Cells

Abstract: The nonbinding 6m-hIGFBP-3 mutant still was able to inhibit DNA synthesis in a mink lung epithelial cell line in which inhibition by wild-type hIGFBP-3 previously had been shown to be exclusively IGF-independent. 6m-hIGFBP-3 only can act by IGF-independent mechanisms since it is unable to form complexes with the IGFs that inhibit their action. We next compared the ability of wild-type and 6m-hIGFBP-3 to stimulate apoptosis in serum-deprived PC-3 human prostate cancer cells. PC-3 cells are known to synthesize a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
128
3
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(138 citation statements)
references
References 69 publications
6
128
3
1
Order By: Relevance
“…These results suggest that the high affinity binding site of IGFBP-6 for IGFs is similar to those of IGFBP-3 and -5 (5,6,24), and that mIGFBP-6 can be used as a tool for studying IGF-independent actions of IGFBP-6.…”
Section: Migfbp-6 Does Not Bind Igfs-to Investigate Potentialmentioning
confidence: 80%
See 2 more Smart Citations
“…These results suggest that the high affinity binding site of IGFBP-6 for IGFs is similar to those of IGFBP-3 and -5 (5,6,24), and that mIGFBP-6 can be used as a tool for studying IGF-independent actions of IGFBP-6.…”
Section: Migfbp-6 Does Not Bind Igfs-to Investigate Potentialmentioning
confidence: 80%
“…A recent crystal structure of a complex comprising the N-domain of IGFBP-4 and IGF-I confirmed this binding site (4). Substitution of these hydrophobic residues in IGFBP-3 and -5 decreased their IGF-I binding affinities Ͼ1000-fold and diminished their effects on IGF actions (5,6). However, another study showed residual IGF binding after similar mutations in IGFBP-3, suggesting other regions are involved in IGF binding (7).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Interestingly, IGFBP-3 has been shown to be pro-apoptotic in a variety of cell lines (4,6,24). This process is thought to be an IGF-independent effect of IGFBP-3 mediated by binding of IGFBP-3 to a surface receptor (25).…”
Section: Discussionmentioning
confidence: 99%
“…IGFBP-3 can both enhance and inhibit the effects of IGF-I in vivo and in vitro depending upon experimental conditions (2)(3)(4)(5)(6). Enhancement of IGF-I action may result from enhanced delivery of IGF-I to its plasma membrane receptor, whereas inhibition may be a consequence of competition between IG-FBP-3 and the type 1 IGF receptor for binding of IGF-I (1,2).…”
mentioning
confidence: 99%